A case of congenital afibrinogenemia complicated with thromboembolic events that required repeated amputations. Issue 3 (April 2015) - Ozdemir, Mehmet A.; Işik, Bilgen; Patiroglu, Turkan; Karakukcu, Musa; Mutlu, Fatma T.; Yilmaz, Ebru; Unal, Ekrem
Abstract : Although congenital afibrinogenemia is a rare autosomal recessive bleeding disorder, it can be more frequently encountered in countries where consanguineous marriages are common. Congenital afibrinogenemia is characterized by the undetectable low level of fibrinogen, which causes hemorrhagic diathesis. Paradoxically, arterial and venous thromboembolic complications can develop in patients with afibrinogenemia, which may cause a diagnostic problem to anyone unfamiliar with its clinical features. We report a case of congenital afibrinogenemia presenting with bilateral ischemic lesions of bilateral foot and ankle that required amputations. The patient was treated with fibrinogen concentrate, low-molecular-weight heparin, aspirin, and nifedipine. In conclusion, arterial and venous thromboembolic complications are rare, but severe complications of afibrinogenemia. The management of thromboembolic complications in patients with afibrinogenemia is a balance game. At one end of the scale, there is a bleeding disorder, and at the other end, there is a thrombosis. This fine adjustment is a job of mastery.